Fundamentals and technical trading: behaviour of exchange rates in the CEECs - Mikael Bask; Jarko Fidrmuc (Bank of Finland, 2006)
We present a model of exchange rates, which incorporates the monetary approach and technical trading, and we present the reduced form based on the minimal state variable solution, where both fundamentals and backward-looking term determine the spot exchange rates.Finally, we estimate the impact of the monetary fundamentals for a panel of Central and Eastern European countries (Czech Republic, Poland, Romania and Slovakia) in the second half of the 1990s as well as the complete model of exchange rate determination for daily data over the more recent free-floating period.
URN:NBN:fi:bof-20140807329
Keywords: C23; F31; F36; 330; foreign exchange market; fundamental analysis; panel cointegration; technical analysis